pH-Responsive Hydrogel Bilayer With Reversible, Bidirectional Bending Behavior - Shojaeifard, Mohammad; Niroumandi, Soha; Baghani, Mostafa (Frontiers in Materials, 2022)
Smart hydrogels are promising materials for shape-shifting structures regarding their large reversible deformation in response to external stimuli in the absence of mechanical loading. Actuators composed of responsive hydrogels have gained significant attention due to their low power consumption, bio-compatibility, fast response, and accessibility. Among these structures, bidirectional hydrogel-based actuators are more fascinating, especially when they have similar reversible bending in both directions. This paper introduces a new design concept of a hydrogel bilayer made of a poly (HEMA-co-DMAEMA) layer and a poly (HEMA-co-AA) hydrogel layer that swells at low and high pH, respectively. This structure is capable of bending in diverse directions while the pH of the aqueous bath alters. The main characteristic of this structure is having reversible bidirectional bending, which has similar behaviors in both directions, unlike previous hydrogel-elastomer bilayers. Then, we develop an analytical method to solve the swelling-induced bidirectional bending of a pH-sensitive hydrogel bilayer. On the other hand, the finite bending of bilayer structure is studied by the finite element method in several cases to demonstrate the validity and accuracy of the proposed analytical solution. Lastly, the impacts of material composition and geometrical factors are investigated to be used for bilayer actuator design and application.